Археологічна розвідка по «Шляху Мономаха» - Коваленко, В.П.; Моця, О.П.; Скороход, В.М. (Археологічні дослідження в Україні, 2009)
Presented are the results of archaeological prospecting for the study of Ancient Rus monuments situated along the hypothetical old way from Chernihiv to Kyiv.